Challenges faced in the use of fieldtrips in the teaching and learning of history at ordinary level in Gwanda South District - Moyo, Ngakhile (Midlands State University, 2020)
There are several methods of teaching that can be used in the teaching and learning of History at Ordinary Level. Field work activities in History present students with a chance to interact with the physical and human environment and try to draw relationships between the two. An understanding of these interaction creates an awareness of how human being should interact and draw future conclusions. Fieldwork presents the chance to interact and understand the relationships and processes that shape the world physically, socially economically and politically. Despite its valuable role in the History teaching, the method has not been used in most schools. The study, therefore, sought to establish challenges faced in the use of fieldtrips in the teaching and learning of the History. Due to the nature of the research, a qualitative approach was adopted employing the descriptive survey research design. Sixteen secondary schools in Gwanda South District made up the population and 3 of these schools made the sample. Random sampling was done in the selection of schools. Data were collected through distribution of the questionnaire, personal interviews and document analysis. The gathered data were presented in tables, pie charts, and bar graphs. Thematic and comparative analysis followed the presentation of data. Noted challenges included time, finance, teachers’ incompetence, nature of syllabus and many others. The researcher recommends that parents need to be educated on the importance of field trips in teaching and learning of History so that they will become supportive. Students should be punished for misbehaving during the field trip so that field trips may succeed and play an important role in as far as teaching and learning of History is concerned. Teachers should also be competent enough to use fieldtrips in the teaching and learning and the school administrators should give enough support.